2001
DOI: 10.1002/pola.10027
|View full text |Cite
|
Sign up to set email alerts
|

Amine–quinone polyimides

Abstract: Two dianiline monomers were prepared by the reaction of either 4,4Јmethylenedianiline or 4,4Ј-oxydianiline with 1,4-benzoquinone. These monomers were used to synthesize a series of amine-quinone polyimides by condensation with either 3,3Ј,4,4Ј-benzophenonetetracarboxylic dianhydride or 4,4Ј-(hexafluoroisopropylidene) diphthalic anhydride to make the corresponding polyamic acid. The polyamic acids were converted to the polyimides by thermal imidization at 290°C. The amine-quinone polyimides gave freestanding fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…It is observed that the lap‐shear strength increases from 134.3 to 189.5 MPa when the BB content is increased from 0 to 4 wt%. This result can be attributed to the addition of hydrophobic BB into the epoxy resins which increases the adhesion of the aluminum–epoxy systems through chemical interaction, mediated by the quinone molecule free electrons to the outer orbital of the metal surface through chemisorption 9–11, 20. A similar observation was made with quinone‐amine polyurethanes obtained from toluene diisocyanate, polytetrahydrofuran, and amine‐quinone monomer 21…”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…It is observed that the lap‐shear strength increases from 134.3 to 189.5 MPa when the BB content is increased from 0 to 4 wt%. This result can be attributed to the addition of hydrophobic BB into the epoxy resins which increases the adhesion of the aluminum–epoxy systems through chemical interaction, mediated by the quinone molecule free electrons to the outer orbital of the metal surface through chemisorption 9–11, 20. A similar observation was made with quinone‐amine polyurethanes obtained from toluene diisocyanate, polytetrahydrofuran, and amine‐quinone monomer 21…”
Section: Resultsmentioning
confidence: 54%
“…The curing agent was 4,4′‐diaminodiphenyl methane (DDM), purchased from Aldrich. BB was synthesized as described in recent work 9, 12. Dimethylacetamide (DMAc) as a solvent for BB was supplied from Aldrich.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…More water can easily permeate into this phase due to its less highly cross-linked structure. This leads to a lower T g [12,13]. The higher cross-linked phase had a higher T g and was characterized as the less plasticized phase [14].…”
Section: Neat Epoxy Resinmentioning
confidence: 99%
“…Aromatic polyimide (PI) material, possessing excellent comprehensive properties, has been wildly applicated in aviation, aerospace, 1 automobile, electrical appliances, 2 micro‐electronics, 3 separation membranes 4 and other fields 5 . Due to its stable aromatic heterocyclic structure, PI presents remarkable temperature resistance (−269 ~ 400°C), excellent thermal and chemical stability, 6 outstanding mechanical properties, 7 radiation resistance and other significant characteristics 8,9 . At present, the traditional synthesis method is that the precursor polyamide acid (PAA) has to be synthesized with high molecular weight to get high performance, 10,11 which generated high viscosity in solution, therefore restricting the subsequent processing, especially when PI is used in coatings, 12 films, 13 adhesives and photoresists 14 …”
Section: Introductionmentioning
confidence: 99%